2020
DOI: 10.5114/pjp.2020.97122
|View full text |Cite
|
Sign up to set email alerts
|

Pan-p63 but not ΔNp63 (p40) expression in undifferentiated carcinoma of the pancreas

Abstract: Undifferentiated carcinoma of the pancreas (UC) is a carcinoma without a definitive direction of differentiation. Tumour protein p63 is a regulator of squamous phenotype, which may also be engaged in tumour development. N-terminal isoforms of p63 are TAp63 and ΔNp63. Pan-p63 antibodies are able to detect both isoforms, whereas p40 antibodies recognise the ΔNp63 isoform only. The aim of the study was to describe pan-p63/p40 immunohistochemical expression patterns in pancreatic neoplasms: UC, ductal adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
(241 reference statements)
0
3
0
Order By: Relevance
“…Tianze Zhang found that transcription factor p53 suppresses tumor growth by prompting pyroptosis in nonsmall-cell lung cancer [40]. N-terminal isoforms of p63 are TAp63 and ΔNp63 [41]. The findings of the present study suggested that lncRNA RP1-85F18.6 may trigger colorectal cancer cell proliferation, invasion and cell cycle disruption, and suppress apoptosis and pyroptosis of colorectal cancer cells through regulating ΔNp63 expression [42].…”
Section: Discussionmentioning
confidence: 49%
“…Tianze Zhang found that transcription factor p53 suppresses tumor growth by prompting pyroptosis in nonsmall-cell lung cancer [40]. N-terminal isoforms of p63 are TAp63 and ΔNp63 [41]. The findings of the present study suggested that lncRNA RP1-85F18.6 may trigger colorectal cancer cell proliferation, invasion and cell cycle disruption, and suppress apoptosis and pyroptosis of colorectal cancer cells through regulating ΔNp63 expression [42].…”
Section: Discussionmentioning
confidence: 49%
“…Another research on undifferentiated pancreatic cancer (UC) discovered moderate-to-strong pan-p63 expression in anaplastic (pleomorphic giant cell) UC (n = 4), sarcomatoid UC (n = 2), UC with osteoclastlike giant cells (n = 3), and ductal carcinomas with partial squamous differentiation (n = 3). Pan-p63 expression was observed to be weak and localized in monomorphic UC (n = 3) and in the majority of neuroendocrine carcinomas (6/7 cases) (Liszka, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al found that transcription factor p53 suppressed tumor growth by prompting pyroptosis in non-small-cell lung cancer [ 41 ]. N-terminal isoforms of p63 are TAp63 and ΔNp63 [ 42 ]. These findings suggested that lncRNA RP1-85F18.6 may trigger colorectal cancer cell proliferation, invasion and cell cycle disruption, and suppressed the apoptosis and pyroptosis of colorectal cancer cells through regulating ΔNp63 expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%